RELATIONSHIP OF HOME SANITARIAN WITH THE EVENT OF PULMONARY TUBERCULOSIS - Nelson Tanjung; Siti N Sagala (Fakultas Kesehatan Masyarakat Institut Kesehatan Medistra Lubuk Pakam, 2022)
Pulmonary tuberculosis is a disease caused by Mycobacterium tuberculosis and has infected nearly a third of the world's population with 1.5 million deaths due to pulmonary tuberculosis. This disease is closely related to slum and unhealthy environmental conditions, poor sanitation conditions, lighting, occupancy density, ventilation, and room humidity are related to the occurrence of pulmonary tuberculosis. The study used observational analytic methods, the design used case control. The population is all who suffer from tuberculosis. Data were collected and analyzed univariate and bivariate with Chi Square test with 95% confidence level. The results obtained ventilation with p value = 0.003, OR = 0.057, lighting with p value = 0.259, OR = 0.108, humidity with p value = 0.001, OR = 0.444, temperature with p value = 0.056, OR = 0.111, and occupancy density with p value = 0.003, OR = 0.141. There is a relationship between ventilation area, occupancy density, and humidity with tuberculosis. There is no relationship between temperature and lighting on the incidence of tuberculosis.